PERAN KEGIATAN EKSTRAKURIKULER PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENANAMKAN NILAI-NILAI AQIDAH SISWA SMK PGRI 6 NGAWI - Joko Purnomo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2020)
Abstract: This study aims to determine: 1) The process of extracurricular activities for Islamic Religious Education at SMK PGRI 6 Ngawi, 2) The values ​​of aqidah that are applied in extracurricular activities of Islamic Religious Education at SMK PGRI 6 Ngawi. This research was conducted at SMK PGRI 6 Ngawi. This type of research is a case study in field research (field research). The technique of determining the research subject uses non-probability sampling with purposive sampling, which determines the sample with certain considerations and goals. In this study, the subjects of the study were teachers of Islamic Religious Education extracurricular activities and students participating in extracurricular activities of Islamic Religious Education. Data collection techniques using observation, interviews and documentation. The data analysis technique uses the analysis stages of Lexy J Moleong, namely data collection, data reduction, data presentation and conclusion drawing. Based on the results of data analysis, the research results obtained are: 1) the process of extracurricular activities for Islamic Education at SMK PGRI 6 Ngawi is carried out every Thursday-Saturday from 13.00 - 16.00 hours and has full support from the head and teachers of SMK PGRI 6 Ngawi, 2 ) the values ​​of aqidah contained in the extracurricular activities of Islamic Religious Education at SMK PGRI 6 Ngawi are the implementation of the pillars of faith which are summarized in the competence of faith, namely: feeling the supervision of Allah SWT in all actions; pray diligently; thankful diligently; learn to be patient; learn tawakkal; learn piety and try to avoid immorality.